A POLYPHONIC DICTATION AS A FORM OF WORK ON HARMONIOUS HEARING - Zavadska, Galina; Bagele, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Harmonious hearing is one kind of musical hearing that manifests itself in relation to a simultaneous sounding of consonances (a complex of sounds of different pitch) and mutual relationships between consonances. A polyphonic music dictation is one of the most important and complicated forms of work for the development of harmonious hearing during sol-fa classes at a higher education establishment. The skill of remembering a polyphonic dictation and quickly fixing the heard music involves an organic combination of listening to separate sounds and to the harmonious vertical of sounds, as well as their functional interaction, which promotes the development of musical thinking in general. The given research is concerned with the comparison of the methodological recommendations for fixing polyphonic dictations, as well as with working out the algorithm of the polyphonic dictation notation. Research aim: to study the principles of a polyphonic dictation and specificity of its notation. Work on a polyphonic dictation implies an organic combination of hearing separate voices and the harmonious vertical, comprehending each moment of sounding and their functional-logical interconnection.